PENGARUH JENIS KAYU DAN SISTEM SAMBUNGAN TERHADAP DESAIN MEBEL KAYU - Eko Agung Syaputra; Imam Damar Djati (Jurnal Penelitian Hasil Hutan, 2021)
Wooden furniture is one of strategic commodities that have a dominant contribution to Indonesian economy compared to otherfurniture material. Joining system in the wooden furniture is the weakest construction point, therefore detail analysis is needed tostudy factors affecting construction capacity and effectiveness of wooden joining system. The aim of this research was to determine theeffect of wood species and joining system on wooden furniture design especially compression strength on joining point. The wood speciesused were jati (Tectona grandis L. f.), kapur (Dryobalanops sp.), meranti (Shorea sp.), manglit (Manglietia glauca Bl.),and sengon (Falcataria moluccana L.). The joining system applied in this study were tenon and mortise, lap, and dovetail joints.The results showed that teak wood exhibited the highest compression strength, while sengon wood exhibits the lowest compressionstrength on all wood joining systems compared to other wood species studied. In term of wood joining systems, the lap joint exhibitedthe highest compression strength, whereas tenon and mortise joint exhibited the lowest performance.